SIMPLIFIED METHOD OF CALORIMETRIC MEASUREMENTS OF BACKGROUND LOSS IN CRYSTALS - V. G. Savitski; A. Kemp (Приборы и методы измерений)
We report on the measurements of absorption coefficient of the synthetic diamond crystal using an adapted form of laser calorimetry technique at wavelengths of 1064, 640, 532, 452 and 364 nm. The absorption coefficient was found to increase exponentially from 0,03 cm-1 at 1064 nm to 0,7 cm-1 at 364 nm.